AD, Volume 5, n° 4, 1980 - Full Issue (Africa Development, 1980)
CONTENTS - SOMMAIRE Sciences Sociales et Développement CLAUDE AKE ......................... 6 The Evolution of Social Sciences in Africa: Problems and Prospects S.A. BUJRA & T. MKANDAWIRE ................. 21 National Objectives and Inter-University Cooperation in Africa: An Unresolved Dilemma PAUL Β. VITTAE ......................... 41 Social Science and Policy: The Nigerian Experience A.O. SANDA ............................. 49 The Impact of the Social Sciences on the Development and Planning of Social Welfare Services in Nigeria ADA A. MERE ......................... 60 Sciences Sociales et Société: Cas du Nigéria S. KODJO ............................. 68 BOOK REVIEWS Planification et Développement en Algérie 1962—1980 par Abdellatif BENACHENHOU B. FOUNOU-TCHUIGOU ........................ 93 Harmonization of African Foreign Policies, 1955—1975: The Political Economy of African Diplomacy TIMOTHY M. SHAW ......................... 100 FOCUS ON RESEARCH & TRAINING INSTITUTES Institute of Development Studies, University of Dar-es-Salaam, Tanzania ..................... 102 ON WALTER RODNEY